An economic-business approach to clinical risk management - Ubaldo Comite; Kechen Dong; Rita Yi Man Li; M. James C. Crabbe; Xue-Feng Shao; Xiao-Guang Yue (Journal of Risk and Financial Management, 2020)
This paper introduces risk factors in the field of healthcare and discusses the clinical risks, identification, risk management methods, and tools as well as the analysis of specific situations. Based on documentary analysis, an efficient and coherent methodological choice of an informative and non-interpretative approach, it relies on "unobtrusive" and "non-reactive" information sources, such that the research results are not influenced by the research process itself. To ensure objective and systematical analysis, our research involved three macro-phases: (a) the first involved a skimming (a superficial examination) of the documents collected; (b) the second reading (a thorough examination) allowed a selection of useful information; (c) the third phase involved classification and evaluation of the collected data. This iterative process combined the elements of content and thematic analysis that categorised the information into different categories which were related to the central issues for research purposes. Finally, from the perspective of safety analysis and risk management, we suggest that comprehensive control and operation should be conducted in a holistic way, including patient safety, cost consumption, and organizational responsibility. An organizational strategy that revolves around a constant and gradual risk management process is an important factor in clinical governance which focuses on the safety of patients, operators, and organizations.
Keywords: 330; risk management; clinical risk; welfare; patient; safety